Analysis of Anthropometric Factors and Physical Conditions Determining Feeder Skills in Sepaktakraw - Laksono, Valentinus Bismo Tri; Rahayu, Setya (Jurnal Porkes, 2025)
This study aims to analyze the anthropometric factors of physical conditions that have a dominant influence on the feeder's ability in sepaktakraw. This study applies a quantitative approach with an associative research type. Associative research aims to identify the relationship or influence between two or more variables. In this study, two types of statistical analysis were used, namely simple correlation tests and multiple linear regression tests. The research sample was taken using a purposive random sampling technique of 15 athletes. Data were collected through anthropometric tests, physical condition tests, and feeder tests in sepaktakraw sports. Furthermore, the data obtained were analyzed using the SPSS application. The results of this study indicate that the variables that do not significantly affect feeder skills with the partial test method (t-test) are height 0.858, body mass index 0.087, leg length 0.558, aerobic endurance 0.147. Thus, in this study the anthropometric factors that have a dominant influence on sepaktakraw feeder skills are the length of the sole of the foot, while the physical condition factor that has a dominant influence on sepaktakraw feeder skills is agility. This finding is expected to enable Central Java sepak takraw coaches to pay attention to the anthropometric components and physical conditions that have a dominant influence on improving sepak takraw performance.